EFFECT OF PLAY ON ANXIETY OF HOSPITALIZED CHILDREN - S Khanjari; Mola, F; Davachi, A; Haghani, H (Iran University of Medical Sciences, 2001)
Background : Hospitalization is an anxiety producing event for children and their families, There are many strategies to reduce the anxiety of hospitalized child one of which is play.   Objective : To determine the effect of Play on the anxiety of hospitalized children.   Design : This study was a randomized clinical trial with control group. At the beginning of trial the anxiety of both groups were measured by "spiel Berger's questionnaire". Then the children of trial group had the chance of playing in play room for half an hour. One and five hours after playing both groups completed the same questionnaire again.   Samples : 92 school age children in hospital were randomly assigned in two groups. 46 in control group.   Results : The findings indicated that the play reduced the anxiety of children in case group after one hour, but the effect of play did not last long (5 hours afterwards).. Conclusion : We can decrease the anxiety of hospitalized children by providing play room. Nurses should provide opportunity for hospitalized children to play. For the continuity of play it is suggested that the hospitals' play rooms be active during day. It id recommended that effect of play on anxiety of hospitalized children who are isolated or on complete bed rest or are in ICU be assessed